USING PICTURE TO IMPROVE STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXTS AT 8Th GRADE STUDENTS OF SMP N 1 SIAU TIMUR SELATAN - Fortunandini Kilapong; Nurmin Samola; Fivy Andries (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of the study is to describe whether using picture can improve students’ reading comprehension. This research involved the Eight-grade students of SMP N 1 Siau Timur Selatan were 22 students as the research subject. The design of this research is the pre-experimental design with one group pre-test and post-test and the instrument used in collecting the data was a test. The data were analyzed by using the mean score. The finding shows that this research came out with finding that using picture is effective can improve students reading comprehension. The difference in student scores on T1 & T2 where the mean score of T1 was 64.54 and the mean score of T2 was 78.18. These results indicate that the use of picture in teaching reading comprehension is effective to improve students reading comprehension. This also shows that the use of picture in learning activities at SMP N 1 Siau Timur Selatan was effective to improve students reading comprehension. Therefore, it is suggested that teacher of English subject in SMP use picture in teaching reading comprehension to their students.